Validation of the modified Japanese Triage and Acuity Scale-based triage system emphasizing the physiologic variables or mechanism of injuries - Funakoshi, Hiraku (Int J Emerg Med, 2016)
BACKGROUND: The Canadian Triage and Acuity Scale is a valid triage system. The system was translated and implemented in the Japanese emergency departments (EDs) from 2012. This system was named the Japanese Triage and Acuity Scale; however, the validation studies of the Japanese Triage and Acuity Scale have been limited. In addition, for a patient with multiple complaints, it could become challenging, due to its requirement of a single complaint. Therefore, we hypothesized that a modified version of the Japanese Triage and Acuity Scale using first-order modifiers without chief complaint detection is accurate. METHODS: A retrospective cohort study evaluated a correlation between the modified triage scale level and outcomes of all adult emergency department patients at a Japanese hospital. Construct validity of the modified triage scale level was assessed based on comparisons of total admission rate (including hospitalizations, emergency department deaths) and length of stay between triage levels. RESULTS: The distributions of five levels of the triage scale (level 1 is the most urgent) among the 17,121 cases are as follows: 1:451, 2:1148, 3:7703, 4:7652, and 5:167. Total admission rates by each level were 1:89.8, 2:68.2, 3:26.4, 4:6.6, and 5:0.6 %, which progressively increased from level 5 to 1 and were significant (p < 0.01). Compared with patients in level 3, the odds of total admission rates were 14.4, 5.1, 0.27, and 0.030 for the patients in levels 1, 2, 4, and 5. The length of stay was longer in the patients with the more urgent levels except for those with level 1. CONCLUSIONS: The modified version of the Japanese Triage and Acuity Scale is a valid predictor of total admission and length of stay and may enable the nurses to triage patients without detecting the chief complaints.